Ukraine Strategy for Financial Services Consumer Protection and Financial Literacy (2012-17) : Diagnostic Review and Action Plan, Volume 1. Main Findings and Recommendations - World Bank (World Bank, Washington, DC, 2017)
Eight years of strong economic growth in Ukraine in 2000-2008, at an average of seven percent per year, ended with a sharp 15 percent decline in 2009. The national currency plummeted and the banking sector nearly collapsed, with non-performing loans increasing from 2.3 percent to 11.2 percent of total loans in 2008-2010. According to the 2010 USAID/FINREP financial literacy survey, 39 percent of adult Ukrainians are still unbanked and nearly half prefer holding savings in cash. Only 15 percent of consumers trust banks and just 6 percent trust investment funds or private pension funds. Only 17 percent believe in a fair resolution in a dispute with a financial institution. The Ukrainian authorities recognize that the financial system needs to be made more resilient to future crises and thus requires a substantial redesign of the legal and regulatory framework of consumer protection and market conduct in financial services. This World Bank's diagnostic review aims to help Ukraine design a 5-year strategy to strengthen financial consumer protection and financial education as the fundamentals for sustainable growth and deepening of the financial sector. The review is presented in two volumes. Volume I contains the main findings and recommendations of the review, and Volume II provides a detailed assessment of Ukraine's compliance with the international best practices summarized in the World Bank's Good Practices for Financial Consumer Protection.